Evaluasi Beban Kerja Guna Penjadwalan Ulang Shift Kerja Dengan Metode National Aeronautics and Space Administration Task Load Index Pada Dosare Hotel Yogyakarta - Dwiky Kurniawan; Naufal Syauqi Bimadhieka Nk; Mutia Kanzha Putri Santoso; Nila Wati; Isnoe Faqih Hidayat (CV. ALIM'SPUBLISHING, 2025)
. This study aims to evaluate the mental workload of employees at Dosare Hotel Yogyakarta using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method and propose an optimal work schedule. Dosare Hotel, operating with five employees across three shifts, faces challenges of excessive workload during periods of high guest occupancy. The study result show that employees with the highest NASA-TLX scores experience a high mental workload, while others fall into the moderate category. The proposed solutions include two scheduling options: hiring one permanent employee at a cost of IDR 15.000.000 per month or adding one outsourced worker at a cost of IDR 12.900.000 per month. This rescheduling is expected to improve work efficiency, maintain employee health, and minimize operational cost.